Pengaruh Sifat Kepribadian dan Tingkat Pendidikan Terhadap Kinerja Auditor (Studi Empiris Pada Auditor yang Bekerja di KAP Jojo Sunarjo & Rekan) - Maharani, Melinda; Indrati, Menik (Universitas Sains dan Teknologi Komputer, 2025)
The study aims to analyze the influence of Self-esteem, narcissism, Knowledge Sharing, professional skepticism, and Educational Level on Auditor Performance. The research was conducted with auditors at the Public Accounting Firm Jojo Sunarjo & Partners to understand how psychological characteristics, professional behaviour, and educational background contribute to optimal auditor performance. The study included 202 active auditors. Data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach with SmartPLS version 4.0. The results show that Self-esteem, Knowledge Sharing, Professional Skepticism, and Educational Level positively influence Auditor Performance. Meanwhile, Narcissism has an adverse effect on Auditor Performance. These findings highlight the importance of personality traits and professional conduct in supporting the quality of auditor performance.